Microlearning in the Final Degree Project (FDP) subject - Gallent Torres, Cinta (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article aims to give continuity to a pilot project carried out in the Master’s Degree in Teacher Training at the International University of Valencia in 2021-2022. Based on its implementation, results and evaluation, it has been decided to improve the project this academic year 2022-2023 by including some methodological changes and tutoring activities for postgraduate students taking the master’s degree final project subject in this degree. These changes are expected to lead to an improvement in teaching quality in this subject and can also be emulated in other degrees.